Parasites on the hop: Captive breeding maintains biodiversity of Eimeria communities in an endangered marsupial. (August 2016) - Vermeulen, Elke T.; Lott, Matthew J.; Eldridge, Mark D.B.; Power, Michelle L.
Abstract: The complex parasite communities of animals contribute to biodiversity, yet the conservation strategies that aim to preserve individual threatened species often overlook their parasite communities. Deeper understanding of parasite communities and how they are affected by management is important to the ultimate success of biodiversity conservation. Here we examine the dynamics between the coccidian parasite Eimeria and the threatened brush-tailed rock-wallaby ( Petrogale penicillata, BTRW) to determine how parasite communities respond to the conservation management practices of captive breeding and translocation. Three BTRW population categories (wild, captive bred or supplemented) were analysed for Eimeria prevalence and infection intensity and a metagenomic assessment performed to examine community structure. Eimeria prevalence was 92% in 117 faecal samples. DNA amplicons from purified oocysts were sequenced with the Illumina MiSeq platform and the resulting sequences assigned to 28 Eimeria operational taxonomic units (OTUs). Pairwise identity between OTUs was 89.9% and 25 of the Eimeria OTUs formed a highly supported phylogenetic clade with marsupial specific Eimeria species, indicating strong host specificity and genetic diversity within Eimeria in BTRWs. Supplemented populations had the greatest OTU diversity with eleven unique OTUs and had a greater overlap with captive bred (9 shared OTUs) versus wild populations (6 shared OTUs). There was no significant effect of population category on infection intensity ( p  = 0.965), OTU composition ( p  = 0.51) or richness ( p  = 0.490), suggesting that Eimeria community structure is maintained under the management processes applied to the BTRW. Our approach can be applied to other parasite communities in hosts under conservation management. Graphical abstract: Highlights: Eimeria communities were analysed in wallaby populations in a conservation program. Eimeria was almost ubiquitous across all populations with 92% prevalence. Conservation management had no significant effect on infection intensity of Eimeria . Eimeria community structure was analysed with next generation sequencing. The biodiversity of Eimeria communities was conserved across populations.